CERCETAREA CONTEAZĂ, CERCETAREA SALVEAZĂ! - KULIKOVSKI, Lidia (BIBLIOPOLIS, 2020)
The importance of the research as expression of maturity of a field, or institution is obvious. The Municipal library has a consolidated tradition in research of the subjects specific for the infodocumentary, cultural, literary and historic fields. The achievements of the library, recognized by the research community are due to the BM potential to put goals that meet the Chisinau community expectations. The author notifies that the disponibility to research differs from branch to branch, from librarian to librarian. The author is building the article as a advocacy of the research, aimed to encourage/ motivate the participation of the librarian in research.